GOVERNMENT INITIATIVES FOR ECONOMIC DEVELOPMENT OF TELANGANA STATE (International Journal of Food and Nutritional Sciences, 2022)
The State of Telangana was formed in June 2014 post the split of erstwhile Andhra Pradesh state. Telangana economy has got a major shift in recent decade with a great focus on Primary, Secondary and Tertiary sector as it initiated various development programmes and schemes since the formation of new government with an aim to establish Bangaru Telangana. The government of Telangana is forging ahead for the realization of Bangaru Telangana by balancing the wheels of development through strengthening of all the sectors by initiating new development programmes and schemes. Sustainable Development Goals (SDGs) for Bangaru Telangana which entails sustained efforts for improving infrastructure facilities for overall development in both in rural and urban parts of the state. As a result, Telangana’s Real Gross State Domestic Product (GSDP) at current prices grew by 11.2 percentage while that of the country’s real GDP grew by 8.9 percentage, higher than the national growth rate by 3.6 percentage points, in the year 2021-22. State Per Capita Income (PCT) in current prices is Rupees 2,78,833 while national figure is 1,49,848 in 2021-22 (AE). Thus, the state economy was resilient to the challenges imposed by the COVID-19 pandemic